How to Efficiently Allocate Houses under Price Controls? - Tommy Andersson; Zaifu Yang; Dongmo Zhang (Lund University, School of Economics and Management, Department of Economics, 2014)
Price controls are used in many regulated markets and well recognized as the cause of market inefficiency. This paper examines a practical housing market in the presence of price controls and provides a solution to the problem of how houses should be efficiently allocated among agents through a system of prices. We demonstrate that the dynamic auction by Talman and Yang (2008) always finds a core allocation in finitely many iterations, thus resulting in a Pareto efficient outcome.
Keywords: C71; D44; D47; 330; Ascending auction; assignment market; price control; Pareto efficiency; core